2017
DOI: 10.1038/s41598-017-00456-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of p62 in the suppression of inflammatory cytokine production by adiponectin in macrophages: Involvement of autophagy and p21/Nrf2 axis

Abstract: Adiponectin possesses potent anti-inflammatory properties. p62, an adaptor protein composed of multi-functional domain, is known to play a role in controlling inflammatory responses. In the present study, we examined the role of p62 in suppressing inflammatory cytokines produced by globular adiponectin (gAcrp) and the potential underlying mechanisms in macrophages. We demonstrated that gAcrp significantly increased p62 expression. Knockdown of p62 abrogated the suppressive effects of gAcrp on LPS-stimulated TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
(85 reference statements)
3
27
0
Order By: Relevance
“…There are two ways how administering p62DNA can lead to the anti-inflammatory effect, either directly influencing p62 level in the cells of the target organ or acting indirectly. Cells of the mammal organisms naturally express p62, also known as p62/sequestosome-1 (p62/SQSTM1), which plays a variety of biological roles ranging from oxidative stress, tumorigenesis, autophagy and degradation of misfolded proteins to inflammation and anti-inflammatory response ( Figure 6 ) [ 16 , 25 ]. For instance, p62 inhibited MYD88-TRAF6 complex formation, suppressing expression of IL-6 and nitric oxide synthase 2 [ 26 ]; and p62 overexpression decreased inflammatory cytokines production [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two ways how administering p62DNA can lead to the anti-inflammatory effect, either directly influencing p62 level in the cells of the target organ or acting indirectly. Cells of the mammal organisms naturally express p62, also known as p62/sequestosome-1 (p62/SQSTM1), which plays a variety of biological roles ranging from oxidative stress, tumorigenesis, autophagy and degradation of misfolded proteins to inflammation and anti-inflammatory response ( Figure 6 ) [ 16 , 25 ]. For instance, p62 inhibited MYD88-TRAF6 complex formation, suppressing expression of IL-6 and nitric oxide synthase 2 [ 26 ]; and p62 overexpression decreased inflammatory cytokines production [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“… p62 (SQSTM1) as a mediator of several pathways. Anti-inflammatory effect of p62 can be mediated via inhibition of NF-kB pathway as well as antioxidant response and clearance of damaged proteins/organelles (e.g., mitochondria) [ 25 28 ]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p 21, like p 57, another inhibitor of cyclin‐dependent kinases (CDKs), has been shown to regulate cell cycle arrest and other biological functions, including the regulation of cellular senescence and autophagy. Phosphorylation of p 27(Kip1) at Thr 198 is sufficient to induce autophagy while p 27 depletion can induce the cleavage of poly ADP‐ribose polymerase (PARP) and the activation of caspase‐7, which suppresses autophagy but results in apoptosis . However, little is known about the functions of p57 in autophagy and anti‐ EGFR treatment in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether p57 is a biomarker of anti‐EGFR treatment in HCC is unknown. A study on p21 demonstrated that the expression of p21 critically contributed to the induction of p62, and indicated that the up‐regulation of p21 resulted in the suppression of autophagy . Similar to p21, p57 is also a member of the CIP/KIP family.…”
Section: Introductionmentioning
confidence: 99%
“…In muscle cells, this activity enhances the beta-oxidative pathway, glucose capture, and glycolysis, whereas in hepatocytes, these changes reduce gluconeogenesis [6][7][8][9]. Other responses have linked AdipoR1/R2 to the satiety cycle in the hypothalamus, NOS-induced vascular relaxation in endothelial cells, and inflammatory cascades in macrophages, among others [10][11][12].…”
Section: Introductionmentioning
confidence: 99%